Association of service use with subjective oral health indicators in a freedom of choice pilot - Eero Raittio; Eeva Torppa‐Saarinen; Taru Sokka; Satu Lahti; Auli Suominen; Anna Liisa Suominen; Anna Maria Heikkinen (Wiley, 2023)
Abstract Objectives A freedom of choice pilot provided access to private oral health care services without queuing and with fixed public service‐fees for participants in Tampere region, Finland in 2018-2019. The aim of this study was to investigate how use of oral health care services differed by demographics, socioeconomic status, dental fear, and self‐reported oral health in this pilot. Material and methods SMS‐messages including a link to online questionnaire were sent to participants who had booked an appointment, and to those who had not booked an appointment despite registering to pilot. We categorized participants to (1) those who had booked their first appointment before receiving SMS (visitors), (2) those who booked an appointment after receiving the SMS‐message (late‐visitors), and (3) those who had not booked an appointment during pilot (nonvisitors). We used regression analysis to estimate the association of age, gender, dental fear, economic situation, Oral Health Impact Profile‐14‐severity (oral health‐related quality of life [OHRQoL]), self‐reported oral health and need for oral health care (exposures) with oral health care service use during the pilot (outcome). Results Out of 2300 participants, 636 (28%) responded. Late‐visitors were more likely older and reported more likely need for oral health care, poorer oral health and OHRQoL than visitors or nonvisitors. Nonvisitors were younger and had better OHRQoL than the others. The differences in the service use by gender, economic situation, and dental fear were small. Conclusions Service use during the pilot depended on the subjective oral health. Our findings highlight the potential of reminders in increasing care use among those with perceived need for services.